ANALISIS KEMAMPUAN NUMBER SENSE SISWA SEKOLAH DASAR DI PEKANBARU (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis research aims to know and analyze fifth grade studentsâ competence on number sense in Pekanbaru. Subject in this research were 231 students that 38 students were used as a subject for validation of instruments, and 193 students were a subject for data collection. Survey method was used in this research, and data collection instrumets consist of 15 number sense problems, 10 whole number problems and 5 fraction problems. Data obtained from this research were analyzed using descriptive statistics. The result showed that fifth grade studentsâ competence on number sense in Pekanbaru was still low with the average 51,57. Studentsâ competence on fraction was much lower than whole number. Students also got difficulties in solving number sense problems related to recognise the relative effect of operations on numbers.Key word : Number Sense, Whole Number, Fraction.